An investigation of the potential association between gastrointestinal viral and bacterial infection and development of intestinal acute graft versus host disease following allogeneic hematopoietic stem cell transplantation. Issue 8 (1st March 2021) - Bueno, Felipe; Albert, Eliseo; Giménez, Estela; Piñana, José L.; Pérez, Ariadna; Dolores Gómez, María; Hernández‐Boluda, Juan C.; Gonzalez‐Barberá, Eva M.; Montoro, Juan; Buesa, Javier; Guerreiro, Manuel; Balaguer‐Roselló, Aitana; et al.
Abstract: It is uncertain whether gastrointestinal (GI) infection caused by viral and bacterial pathogens may predispose to gastrointestinal acute Graft‐versus‐host disease (aGvHD‐GI) in allogeneic hematopoietic stem cell transplant recipients (allo‐HSCT). We investigated the potential association between detection of enteropathogenic viruses or bacteria in stools and subsequent occurrence of aGvHD‐GI in a cohort of 121 allo‐HSCT patients. Eighty‐six out of 121 patients (71%) had acute diarrhea and underwent screening for primary GI pathogens by molecular diagnostic methods. One or more GI pathogens were detected in 27 out of the 86 patients with diarrhea (31.3%). Specifically, Clostridioides difficile was found in 16 patients (18.6%), enteropathogenic viruses in 11 patients (12.7%) ( Astrovirus, n  = 4; Norovirus, n  = 2; Sapovirus, n  = 2; Adenovirus, n  = 2; and Rotavirus, n  = 1), and Campylobacter spp. in two patients (2.3%). Thirty patients were diagnosed with all grade aGvHD‐GI by histopathology. Detection of primary GI pathogens was achieved in 12 out of 30 patients ( Clostridium difficile, n  = 5; enteric viruses, n  = 8; Campylobacter spp., n  = 1) who either subsequently developed ( n  = 9) or previously had ( n  = 3) grade I‐IV IaGvHD ( n  = 9). Neither the detection of these microorganisms (all combined), enteric viruses, nor C. difficile was significantly associated with subsequent aGvHD‐GI development in Cox models (hazard ratio [HR] = 1.11, p  = .80; HR = 1.64, p  = .62; HR = 0.75, p  = .64, respectively). Analogous results were obtained when grade II–IV aGvHD‐GI was selected as the clinical outcome. In summary, data in the current study did not support an association between GI infection and subsequent occurrence of aGvHD‐GI in an unselected cohort of allo‐HSCT recipients.